Intrasexual competition enhances reproductive isolation between locally adapted populations. Issue 1 (28th November 2017) - Bierbach, David; Arias-Rodriguez, Lenin; Plath, Martin
Abstract: During adaptation to different habitat types, both morphological and behavioral traits can undergo divergent selection. Males often fight for status in dominance hierarchies and rank positions predict reproductive success. Ecotypes with reduced fighting abilities should have low reproductive success when migrating into habitats that harbor ecotypes with superior fighting abilities. Livebearing fishes in the Poecilia mexicana -species complex inhabit not only regular freshwater environments, but also independently colonized sulfidic (H2 S-containing) habitats in three river drainages. In the current study, we found fighting intensities in staged contests to be considerably lower in some but not all sulfidic surface ecotypes and the sulfidic cave ecotype compared with populations from non-sulfidic surface sites. This is perhaps due to selection imposed by H2 S, which hampers oxygen uptake and transport, as well as cellular respiration. Furthermore, migrants from sulfidic habitats may lose fights even if they do not show overall reduced aggressiveness, as physiological performance is likely to be challenged in the non-sulfidic environment to which they are not adapted. To test this hypothesis, we simulated migration of H2 S-adapted males into H2 S-free waters, as well as H2 S-adapted cave-dwelling males into sulfidic surface waters. We found that intruders established dominance less often than resident males, independent of whether or not they showed reduced aggressiveness overall. Our study shows that divergent evolution of male aggressive behavior may also contribute to the maintenance of genetic differentiation in this system and we call for more careful evaluation of male fighting abilities in studies on ecological speciation.